HUBUNGAN PENGETAHUAN GIZI, ASUPAN GIZI DAN LAMA TIDUR DENGAN INDIKATOR KELEBIHAN BERAT BADAN PADA MAHASISWI FKM UNDIP ANGKATAN 2014-2016 - Vinna Audinni Putri; Siti Fatimah Pradigdo; Martha Irene Kartasurya (Jurnal Kesehatan Masyarakat (Undip), 2018)
The incidence of obesity among Diponegoro University Public Health Bachelor students year 2014-2016 ranged between 14.4% to 21.6% with the tendency of increasing. The purpose of this study was to analyze the correlation between nutritional knowledge, nutritional intake and sleep duration with overweight indicators among Public Health female students year 2014-2016. This study used a cross-sectional design. The subjects  were 100 female students year 2014-2016 who had BMI ≥18,5 kg/m2 and selected by stratified random sampling. Data were collected by interviews using structured quistionnares, physical activity recall, body fat percentage and waist circumference measurements. Data were analyzed by Spearman rank correlation and Pearson correlation test. The results showed that 87% of the subjects has good knowledge, 64% lack of sleep, 84% had low energy adequacy levels, 92% had excessive saturated fat, 82% had excessive unsaturated fat, 100% had simple carbohydrates excess, 32% had percentage body fat in obese category and 19% waist circumference excess. There were correlations between energy adequacy level (r = -0.3531; p = 0.001) and simple carbohydrate intake (r = 0.321; p = 0.001) with body fat percentage. There were correlation between energy adequacy level (r = -0.313; p = 0.002), saturated fat intake (r = 0.202; p = 0.044) and simple carbohydrate intake (r = 0.254; p = 0.011) with waist circumference. It is suggested for the students to reduce the fat and sweet food.